1998
DOI: 10.1007/s004670050402
|View full text |Cite
|
Sign up to set email alerts
|

Creatinine clearance following cimetidine for estimation of glomerular filtration rate

Abstract: Simultaneous inulin (C[in]) and creatinine clearance (C[Cr]) studies were performed on 53 pediatric renal patients using a cimetidine protocol. Since cimetidine blocks the tubular secretion of creatinine, it was hypothesized that C(Cr) measured following cimetidine would closely approximate the C(in). C(in) was compared with C(Cr) with the latter calculated from: (1) a 24-h urine collection, (2) plasma creatinine, height, and a proportionality constant, (3) the same plasma and urine specimens used for calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 20 publications
1
49
1
1
Order By: Relevance
“…The protocol modified by Hellerstein and colleagues used cimetidine for 3 days at a dose of 20 mg/kg in two divided doses (maximum 1,600 mg per day and a sliding scale dose reduction for decreased GFR) [24]. After a final dose of half the daily dose and an oral load of 7-8 ml/kg of fluids, urine is collected for approximately 2 h under supervision [25].…”
Section: Endogenous Creatinine Clearance and The Use Of Cimetidinementioning
confidence: 99%
See 2 more Smart Citations
“…The protocol modified by Hellerstein and colleagues used cimetidine for 3 days at a dose of 20 mg/kg in two divided doses (maximum 1,600 mg per day and a sliding scale dose reduction for decreased GFR) [24]. After a final dose of half the daily dose and an oral load of 7-8 ml/kg of fluids, urine is collected for approximately 2 h under supervision [25].…”
Section: Endogenous Creatinine Clearance and The Use Of Cimetidinementioning
confidence: 99%
“…Such a formula generally provides a good estimate of GFR (r~0.9) when compared with creatinine and inulin clearance data [24,26]. Interestingly, at high values of GFR, the variation between inulin clearance and GFR estimated by the Schwartz formula was about 20%, but it was much smaller at lower levels of GFR [24,26].…”
Section: Estimated Gfr Based On Serum Creatininementioning
confidence: 99%
See 1 more Smart Citation
“…The bias of Schwartz formula estimates compared to creatinine clearances is relatively small; however, the Schwartz formula has been shown to overestimate inulin clearance, particularly in children with low GFR. 168,169,172 Although formulas that estimate creatinine clearance overestimate GFR, they provide an estimate that is accurate enough for K/DOQI National Kidney Foundation Part 5. Evaluation most clinical purposes and represent a better alternative to assessing kidney function than serum creatinine alone.…”
Section: K/doqi National Kidney Foundation Part 5 Evaluationmentioning
confidence: 99%
“…127,[182][183][184][185][186] None of these studies demonstrated substantial improvement in estimating creatinine clearance using a 24-hour or timed urine collection over the use of either the Schwartz or CounahanBarratt prediction equations. One relatively small study 169 Important exceptions may be the estimation of GFR in individuals with variation in dietary intake (vegetarian diet, creatine supplements) or muscle mass (amputation, malnutrition, muscle wasting), since these factors are not specifically taken into account in prediction equations. In these situations, collection of a 24-hour urine sample for measurement of creatinine clearance, or measurement of clearance of an exogenous filtration marker, may provide better estimates of GFR than prediction equations.…”
Section: Measuring 24-hour Creatinine Clearance To Assess Gfr Is Not mentioning
confidence: 99%